Retailer strategies to encourage reduced packaging adoption. (20th June 2022) - Pak, Olga; Galbreth, Michael; Ferguson, Mark
Abstract: Using retail sales data for liquid detergents, we evaluate retailer choices with regards to reduced packaged products and their sales. Our results show that Wal-Mart's decision to force its suppliers to switch to reduced packaged detergent had a market-wide impact and drove non-concentrated liquid detergents from the market. Results also show that retailers, irrespective of market power, may select higher ratios of reduced packaged products and ensure convex levels of sales for those types of products. Highlights: A large retailer with market power can initiate a market-wide shift. Retailers can drive reduced packaged sales by increasing their proportion on the shelf. Stakeholders can work together to impact adoption of environmentally friendly products.